2014
DOI: 10.1155/2014/735292
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Alterations of Chromosome 3 Revealed by NotI-Microarrays in Clear Cell Renal Cell Carcinoma

Abstract: This study aimed to clarify epigenetic and genetic alterations that occur during renal carcinogenesis. The original method includes chromosome 3 specific NotI-microarrays containing 180 NotI-clones associated with 188 genes for hybridization with 23 paired normal/tumor DNA samples of primary clear cell renal cell carcinomas (ccRCC). Twenty-two genes showed methylation and/or deletion in 17–57% of tumors. These genes include tumor suppressors or candidates (VHL, CTDSPL, LRRC3B, ALDH1L1, and EPHB1) and genes tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 37 publications
1
35
0
2
Order By: Relevance
“…It plays an important role in the regulation of B cell development and monocyte differentiation, and participates in cardiac valve morphodifferentiation and lung development [4]. Numerous studies have shown that the expression level of FOXP1 shows a marked change in tumor tissues, being lower in renal, breast, ovarian, lung and prostate cancers than in normal tissues [5][6][7][8][9][10], but is increased in malignant tumors such as lymphoma, which indicates that FOXP1 may have other roles except as an anti-oncogene [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role in the regulation of B cell development and monocyte differentiation, and participates in cardiac valve morphodifferentiation and lung development [4]. Numerous studies have shown that the expression level of FOXP1 shows a marked change in tumor tissues, being lower in renal, breast, ovarian, lung and prostate cancers than in normal tissues [5][6][7][8][9][10], but is increased in malignant tumors such as lymphoma, which indicates that FOXP1 may have other roles except as an anti-oncogene [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Clear-cell renal cell carcinoma (ccRCC) accounts 70-80 % of all renal cancer cases and is characterized by chemo-and radio-resistance [1]. According to the NotI-microarrays, the PPM1M and PRICKLE2 genes showed the presence of methylation/deletion more than in 20 % of ccRCC tumor samples [2]. We performed an analysis of the GEO data base for the PPM1M and PRICKLE2 genes (http://www.…”
mentioning
confidence: 99%
“…This corresponds to a low percentage of methylation/deletion changes in the microarray analysis of these genes [2].…”
mentioning
confidence: 99%
“…Up to 10% of RCC patients present with characteristic clinical symptoms consisting of hematuria, lateral dorsal or flank pain and palpable abdominal mass. Over 60% of RCC are detected incidentally in routine ultrasound examination 7 . Despite the advances in diagnosis, especially improved imaging techniques, about 20-30% of all patients are diagnosed with metastatic disease.…”
Section: Introductionmentioning
confidence: 99%